2017
DOI: 10.3390/met7020068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process and Post-Process Conditions on the Mechanical Properties of an A357 Alloy Produced via Laser Powder Bed Fusion

Abstract: A357 samples were realized by laser powder bed fusion (LPBF) on building platforms heated up to different temperatures. The effect of the preheating temperature and of the post processing heat treatment on the microstructure and the mechanical properties of the samples was studied. It was demonstrated that building platform heating can act as an in situ ageing heat treatment following the fast cooling that arises during laser scanning. A 17% higher ultimate tensile strength was achieved by the selection of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 29 publications
9
36
0
Order By: Relevance
“…[91] In terms of sophisticated designs, which utilize the peculiarities for their benefit, the precise description of the material behavior is required. [91,95,130] Moreover, this inhomogeneity was superimposed with tensile properties which showed a highly dependency to the load versus layer orientation, with maxima of strength and ductility in, or close to, a parallel layer to loading case. Commonly, this is undertaken based on the component's alignment and positioning during manufacture (see Figure 6).…”
Section: Mechanical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…[91] In terms of sophisticated designs, which utilize the peculiarities for their benefit, the precise description of the material behavior is required. [91,95,130] Moreover, this inhomogeneity was superimposed with tensile properties which showed a highly dependency to the load versus layer orientation, with maxima of strength and ductility in, or close to, a parallel layer to loading case. Commonly, this is undertaken based on the component's alignment and positioning during manufacture (see Figure 6).…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…However, it was revealed that AM microstructures react differently to HTs. [130,145,150] A subsequent aging was found to homogenize the microstructure by assimilating the various precipitation [95] Al-3.5Cu-1.5Mg-1Si 223 366 5.3 Φ ¼ 90 [154] AlMgScMnZr 68.0-73.6 >277 >400 Φ ¼ 0 , 90 [116] A t and A g are for most cases in very close proximity, since these Al alloys do not show necking before fracture. [115,216] Thus, representing a local weak spot for the occurrence of brittle fractures along the Si-rich areas, namely the scan track overlaps and the wetting areas between layers (Figure 2b).…”
Section: Tensile Strengthmentioning
confidence: 99%
“…The build platform was pre-heated in order to obtain an in situ aging effect, which made it possible to minimize the anisotropy of the finished part [15] and slow the cooling rate, thus reducing the residual stress state as compared to unheated parts [32]. For this reason, no stress-relieving treatment was performed on the built parts.…”
Section: Am Conditionsmentioning
confidence: 99%
“…A357.0 is a new entry on the market of commercial feedstocks for AM and hence very little is known so far about its properties. In fact, very few papers have been published to date on the production, microstructure, and mechanical properties of A357.0 parts manufactured by L-PBF [32][33][34][35][36]. It is worth noting that such articles are all very recent, since they have been published after 2016, which confirms the growing interest in this new aluminum alloy for L-PBF.…”
mentioning
confidence: 96%
“…The most popular Al-Si alloy processed by LPBF is AlSi 10 Mg alloy (similar to A360). Other Al-Si alloys by LPBF are AlSi 7 Mg (called also A357) [10][11] and AlSi 12 Mg [12].…”
Section: Aluminum Alloys 31 Introductionmentioning
confidence: 99%